MENINGKATKAN KEMAMPUAN MENULIS TEKS EXPOSISI ANALITIS PESERTA DIDIK PELAJARAN BAHASA INGGRIS MELALUI METODE STAD - Euis Sustini (Pedagonal : Jurnal Ilmiah Pendidikan, 2020)
IMPROVING STUDENTS’ ABILITY  IN WRITING ANALYTICAL EXPOSITION TEXT OF ENGLISH LESSONS THROUGH STAD METHODOne of the writing skill was writing analytical exposition text. The teacher saw that the test results of student ability in writing analytical exposition text were disappointing. The dominant students' scores were low. For this reason, the teacher reviewed the use of the learning model that had been applied so that the activities of students and their learning outcomes increased. The purpose of this study was to determine the learning outcomes of students in English lessons on writing analytical exposition text through the cooperative learning using  Students Team Achievement Division (STAD) type in class XI IPA 4 odd semester 2017-2018 academic year of SMA Negeri 9 Bogor. After conducting the research, the results showed that the STAD type of learning model was proven to improve students learning outcomes and made them more enthusiastic in learning English. Before using this learning model, students only obtained an average value of 6, 81 then an increase occurred after uing the STAD type of learning model. On the first cycle the class average was 81.50 and became 86.28 on the second cycle. From the description above, the researcher concluded that applying the cooperative learning model using Student Team Achievement Division type could change the learning situation of students to be active and excited so that there was an increase in student learning outcomes. Therefore, the researcher suggested that the use of the cooperative learning model using  STAD type had to be applied as a variation of another model in teaching English material in schools.